Current Multiplanar Imaging of the Stapes - Henrot, Philippe; Iochum, Sandrine; Batch, Toufik; Coffinet, Laurent; Blum, Alain; Roland, Jacques (American Journal of Neuroradiology, 2005)
PURPOSE: CT analysis of the stapes is difficult in the axial plane (AP), because of its oblique orientation. Oblique axial reformations could provide a more precise analysis of the stapes in normal and pathologic conditions.MATERIALS AND METHODS: CT of the temporal bone was performed in 31 patients. Only the normal side was examined in the AP and oblique axial plane (OAP), in the plane of the stapes superstructure. Conspicuousness of each stapes component was evaluated in both planes by 2 independent readers. Reproducibility between the 2 readers (R1 and R2) and comparison of conspicuousness between the AP and the OAP in the analysis of the stapes crura were evaluated. The normal position of the stapes arch in relationship to the footplate was determined in the OAP by using biometric landmarks.RESULTS: Conspicuousness of the stapes crura was increased by using OAP. The conspicuousness of the anterior crus was enhanced in 38% with the OAP according to R1 (P < .05) and 32% according to R2 (P < .05). The conspicuousness of the posterior crus was enhanced in 35% with the OAP according to R1 (P < .05), but not significantly enhanced in 22% with the OAP according to R2 (P = .095). Analysis of conspicuousness of the stapes crura was reproducible according to the kappa test.A perpendicular line to the footplate intersecting its midportion crosses the stapes head and the long process of the incus in the OAP in normal patients.CONCLUSION: OAP could enhance the CT analysis of the stapes and provide useful biometric landmarks in pathologic conditions.